Mosquito surveillance on U.S military installations as part of a Japanese encephalitis virus detection program: 2016 to 2021. - Mark F Olson; Caroline Brooks; Akira Kakazu; Ploenphit Promma; Wannapa Sornjai; Duncan R Smith; Timothy J Davis (Public Library of Science (PLoS), 2023)
Japanese encephalitis virus (JEV) continues to circulate throughout Southeast Asia and the Western Pacific where approximately 3 billion people in 24 countries are at risk of infection. Surveillance targeting the mosquito vectors of JEV was conducted at four military installations on Okinawa, Japan, between 2016 and 2021. Out of a total of 10,426 mosquitoes from 20 different species, zero were positive for JEV. The most abundant mosquito species collected were Aedes albopictus (36.4%) followed by Culex sitiens (24.3%) and Armigeres subalbatus (19%). Statistically significant differences in mosquito species populations according to location were observed. Changes in land use over time appear to be correlated with the species and number of mosquitoes trapped in each location. JEV appears to be absent from mosquito populations on Okinawa, but further research on domestic pigs and ardeid birds is warranted.